Factors Associated with Anatomic Failure and Hole Reopening after Macular Hole Surgery - Yutong Li; Siyan Jin; Lijun Shi; Hecong Qin; Jinsong Zhao (Journal of Ophthalmology)
A macular hole (MH), particularly an idiopathic macular hole (IMH), is a common cause of central vision loss. Risk factors for nonidiopathic MH include high myopia, cystoid macular edema, inflammation, and trauma. MH is primarily diagnosed using slit-lamp microscopy and optical coherence tomography (OCT). Half of the patients with stage I MHs are treated conservatively and may show spontaneous resolution. The main treatment methods for MHs currently include vitrectomy and stripping of the internal limiting membrane (ILM). However, in some patients, surgery does not lead to anatomical closure. In this review, we summarize the factors influencing the anatomical closure of MHs and analyze the potential underlying mechanisms.